Relationship of Mitral Annular Plane Systolic Excursion (MAPSE) to Left Ventricular Thrombus Formation - Bakalli, A; Georgievska-Ismail Lj; Zahiti, B; Hocinaj, D; Gecaj-Gashi, A; Mrtezani, A (My University, 2014)
Background: Dilated cardiomyopathy is associated by radial and longitudinal contractile cardiac dysfunction. Left ventricular (LV) thrombus is a frequent finding in patients with dilated cardiomyopathy. The main purpose of our study was to evaluate the role of mitral annular plane systolic excursion (MAPSE) in LV thrombus formation in patients with dilated cardiomyopathy by assessing their correlation. Our additional objective was to compare the relationship of average MAPSE to relations of other LV features [LV size, LV ejection fraction (EF), wall motion score index (WMSI), sphericity index-width to length ratio (w/l) of the LV] and LV thrombus developmentMaterial and Methods: This was a prospective cross-sectional study conducted from October 2009 until January 2012 in 100 sinus rhythm patients with dilated cardiomyopathy without anticoagulation therapy. We excluded patients with: swallowing problems, acute myocardial infarction, atrial fibrillation/flutter, severe systolic dysfunction, severe arterial hypertension, valvular disease, and/or mechanical valves. Results: Mean patient age was 58.1±12.7 years and 69% were men. Mean LV EF was 39.1±6.4%, while mean value of average MAPSE was 9.3±2.2mm. LV thrombus was detected in 14% of patients and its presence correlated well with: average MAPSE (r=-0.22, p=0.01), MAPSE of sepatal wall (r=-0.23, p=0.01), MAPSE of lateral wall (r=-0.2, p=0.02), MAPSE of inferior wall (r=-0.22, p=0.01), LV EF (r=-0.21, p=0.02), LV end diastolic diameter (r=0.24, p=0.008), LV end systolic diameter (r=0.31, p=0.0008), WMSI (r=0.22, p=0.01) and w/l (r=0.19, p=0.03). Conclusions: Longitudinal LV dysfunction is associated with LV thrombus formation, as average MAPSE demonstrates a negative correlation with LV thrombus, and its role is similar to LV size, LV EF, sphericity index and WMSI.
Keywords: left ventricular thrombus; dilated cardiomyopathy; MAPSE